Crafty Chloe - DiPucchio, Kelly S. (Atheneum Books for Young Readers, 2012)
Chloe is very good at sewing and crafts and when her best friend's birthday approaches, she not only creates a fabulous gift, she also saves the day for a classmate who had been unkind to her.